Sustainability Policy in Indonesia: Case Study Economic Structure and Determinants in Banjar Municipality - Agus Supriyadi; Tao Wang; Melda Ria Juwita; Rayhan Gunaningrat; Susi Safitri; Giuseppe T Cirella (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2021)
In response to governance shift in Indonesia, a heavy burden of responsibility is placed on local authorities to act in the best interest of its citizenry. This study examined evidence of local government policy, economic structure, and economic growth in the new autonomous city of Banjar Municipality, West Java Province, Indonesia and assessed determinants of regional transformation. The methodology used location quotient, analysis, shift-share analysis, and ordinary least square regression analysis. The findings revealed in the ten-year period of the study on agriculture, business trade, accommodation, other sectors and public service dominated the structure of the economy. In terms of the authority, the Municipality’s policy of sustainability is aimed at protecting the traditional market and developing local road infrastructure—contributing to its economic growth. Sustainability-oriented policies are designed to stress order, control, and accelerate economic activities which regional authorities sometimes considering them as challenging due to transitional requirements and demands